2022
DOI: 10.1021/acs.energyfuels.2c01766
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Pressure Effects in Laminar Flame Propagation of Ammonia: A Comparative Study with Hydrogen, Methane, and Ammonia/Hydrogen

Abstract: As a promising zero-carbon fuel, ammonia (NH3) has attracted great attention in combustion research. Understanding the pressure effects in the laminar flame propagation of NH3 is crucial for its practical applications in gas turbines, internal combustion engines, boilers, and industrial furnaces. In combination with new measurements in a high-pressure constant-volume cylindrical combustion vessel and experimental data in the literature, the pressure effects in the laminar flame propagation of NH3 were explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…91 However, the application of hydrogen energy faces many problems and challenges in terms of storage, transportation, and use. 92 Ammonia, another kind of hydrogen, is a clean hydrogen carrier fuel and a promising hydrogen storage medium. The only products after combustion are water and nitrogen, which have the advantage of being carbonfree.…”
Section: Pressure Dependencementioning
confidence: 99%
See 1 more Smart Citation
“…91 However, the application of hydrogen energy faces many problems and challenges in terms of storage, transportation, and use. 92 Ammonia, another kind of hydrogen, is a clean hydrogen carrier fuel and a promising hydrogen storage medium. The only products after combustion are water and nitrogen, which have the advantage of being carbonfree.…”
Section: Pressure Dependencementioning
confidence: 99%
“…In the face of severe carbon emissions, carbon-free fuels have recently attracted interest, and hydrogen energy is one of the most promising energy sources of the future . However, the application of hydrogen energy faces many problems and challenges in terms of storage, transportation, and use . Ammonia, another kind of hydrogen, is a clean hydrogen carrier fuel and a promising hydrogen storage medium.…”
Section: Advances In the Experimental Study Of The Flammability Limit...mentioning
confidence: 99%
“…Based on a constant-volume combustion chamber (CVCC), Mei et al 15 explored the characteristics of laminar flame propagation of the NH 3 /O 2 /N 2 mixture and found that the mole fraction of key radicals (such as OH, NH 2 , and H) was increased with the elevation of adiabatic flame temperature. Kanoshima et al 16 and Zhang et al 17 evaluated the temperature and pressure effects on ammonia/air flame and observed that compared with those of methane/air flame, ammonia/air flame exhibited a higher temperature exponent and a pressure exponent of near zero. The above studies have yielded valuable insights into NH 3 combustion in IC engines under high-temperature and -pressure conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the presence of the N element in NH 3 molecules, the problem of high NO x emission caused by ammonia fuel needs to be solved. In order to improve the characteristics of ammonia, more reactive fuels can be used for doping with ammonia, such as methane (Valera-Medina et al, 2015) and hydrogen (Zhang et al, 2022). Since methane is the main component of natural gas fuel widely used in gas turbines, using ammonia/methane blends is one way to promote ammonia as an alternative fuel to natural gas (An et al, 2021;Sun J. et al, 2022).…”
Section: Introductionmentioning
confidence: 99%